Mental Accounting in Business and Taxation: A Bibliometric Analysis - Rizka, Nor Rahma; Ulfida, Deafatunnizwa; Izzadieny, Fitra; Rahmi, Audina; Indriyani, Indriyani (Economic and Science Faculty of Islamic State University, 2025)
This study aims to analyze research trends related to mental accounting in business and taxation using a bibliometric approach. This study collected data from Scopus database from 2015-2024 to understand the academic development in this field. The analysis was conducted using bibliometric mapping method using VOSviewer, which includes publication distribution, author influence, keyword network, and thematic evolution. The results show that publications related to mental accounting in the context of business and taxation have increased in the past decade, with a primary focus on tax compliance, financial decisions, and business sustainability. The United States is the country with the highest number of publications, followed by Austria, China, and Indonesia. The study also found that recent research is increasingly pointing towards the integration of mental accounting with business sustainability and green economy strategies. The findings provide insights for academics, practitioners, and policymakers in understanding how psychological factors influence financial decision-making and tax policy.